(untitled) (Indian Journal of Public Health Research & Development, 2026)
Background: Mass gatherings generate sudden, time-limited surges in demand for primary care, triage, emergency referral, and public health surveillance.1,2 Transit point facilities are strategically important but remain underreported in the Indian mass-gathering literature.7,10 This study assessed morbidity profile, service utilisation, and operational outcomes at a 24-hour transit point mini hospital and two first-aid camps during Gangasagar Mela 2026. Methods: A retrospective descriptive observational study was conducted using routinely maintained OPD, emergency, observation, and referral registers from Outram Ghat, Kolkata, for 9-17 January 2026. All eligible patient encounters were included by complete enumeration. Duplicate and incomplete records were excluded. Data were summarized using frequencies and percentages. Chi-square testing, one-way ANOVA, and quadratic trend modelling were used for selected comparisons. Results: A total of 6,480 patients were managed, including 6,472 OPD visits and 8 observation cases. Peak OPD attendance occurred on 12 January 2026 (n=1,037). The leading categories were bodyache (n=1,498, 23.1%), acidity/ dyspepsia (n=955, 14.8%), fever (n=895, 13.8%), common cold (n=654, 10.1%), cough (n=577, 8.9%), and loose motion (n=542, 8.4%). Male patients constituted 62.6% of all patients managed. Referral rate was low (8/6480, 0.12%). Morbidity distribution varied significantly across days (chi-square=798.4, df=96, p<0.001). Conclusion: The transit point mini hospital and first aid camps absorbed a high outpatient burden dominated by self-limiting musculoskeletal, gastrointestinal, febrile, and respiratory complaints, while maintaining safe referral for high-acuity events. The findings support the role of decentralised transit point medical systems, syndromic surveillance, and preventive preparedness in mass-gathering health management.